Immunogenicity and safety of a second booster dose of an acellular pertussis vaccine combined with reduced antigen content diphtheria-tetanus toxoids 10 years after a first booster in adolescence: An open, phase III, non-randomized, multi-center study. Issue 8 (3rd August 2018) - Kovac, Martina; Kostanyan, Lusiné; Mesaros, Narcisa; Kuriyakose, Sherine; Varman, Meera
ABSTRACT: Pertussis is a highly contagious disease, for which periodic peaks in incidence and an increasing number of outbreaks have been observed over the last decades. The reduced-antigen-content tetanus-diphtheria-acellular pertussis vaccine (Tdap) can be used to boost individuals aged ≥10 years, vaccinated in infancy with a diphtheria-tetanus-acellular pertussis vaccine (DTaP), to reduce pertussis morbidity and maintain protection against diphtheria and tetanus throughout adolescence and adulthood. This phase III, open-label, non-randomized, multicenter follow-up study (NCT01738477) enrolled 19–30-year-old participants from the United States who had received booster vaccination 10 years earlier with either Tdap (Tdap group) or Td (Td group). In total, 128 (Tdap group) and 37 (Td group) participants received Tdap vaccination. After administration of Tdap, all participants were seroprotected (antibody concentrations ≥0.1 international units [IU]/ml) against diphtheria and tetanus. Immune responses to a second Tdap dose in the Tdap group were shown to be non-inferior to responses elicited by a first Tdap dose in the Td group for diphtheria and tetanus and to a 3-dose DTaP vaccination during infancy for pertussis antigens (primary objectives). Post-booster vaccination, all participants in both groups had antibody concentrations above assay cut-offs and antibody geometric mean concentrations increased by 3.8–15.5-fold compared to pre-booster levels for all antigens. The incidence of adverse events was similar in the Td (80.6%) and Tdap (85.6%) groups (no serious adverse events reported). A Tdap dose administered after previous Td or Tdap vaccination was shown to be immunogenic and well-tolerated in young adults, supporting repeated vaccination with Tdap at 10-year intervals.